Genetic diversity analysis of aromatic rice (Oryza sativa L.) germplasm based on agro-morphological characterization - Akhtar, Rumana; Iqbal, Adil; Dasgupta, Tapash (ORYZA-An International Journal of Rice, 2022)
Aromatic rice is a special class of rice known in the Indian subcontinent. A total of fifty-eight aromatic rice genotypes were evaluated on the basis of 12 agro-morphological traits at Agricultural Experimental Farm, University of Calcutta, Baruipur, West Bengal to characterize and estimate genetic diversity. Phenotypic coefficient of variation exhibited higher values but maintained close relation with genotypic coefficient of variation for all the traits. Additive gene action was prominent for traits like plant height, panicle length, number of filled grains per panicle and 1000 grain weight. A correlation study showed that grain yield per plant was positive and significantly correlated with tillers per plant, panicles per plant, number of filled grains per panicle, total number of filled grains per plant and 1000 grain weight. The principal component analysis revealed that total number of filled grains per plant had a strong relation with grain yield. Based on Manhattan clustering, fifty-eight genotypes were grouped into five distinct clusters. 24 genotypes in cluster III,17 in cluster I, 9 in cluster II,7 in Cluster IV and 1 genotype in Cluster V.